Role of the NMDA Receptor in the Antitumor Activity of Chiral 1,4-Dioxane Ligands in MCF-7 and SKBR3 Breast Cancer Cells - Morelli, Maria Beatrice (ACS Med Chem Lett, 2019)
[Image: see text] The potent N-methyl-d-aspartate (NMDA) receptor antagonists 1–3 have been demonstrated to show antiproliferative and cytotoxic effects in MCF-7 and SKBR3 breast cancer cell lines. To improve the knowledge about the role played by the NMDA receptor in the antitumor activity of these compounds, the enantiomers of 1 were prepared and evaluated for their affinity for the phencyclidine (PCP) site of the NMDA receptor and for their cytotoxic effect in MCF-7 and SKBR3 cell lines, both expressing the NMDA receptor. The (S)-1 enantiomer, showing negligible affinity for the PCP site, exhibited antiproliferative activity higher than that of (R)-1, which instead bound the PCP site. The downregulation of NMDA GluN1 expression resulted in a decreased (S)-1-induced cytotoxicity and apoptotic cell death, unequivocally demonstrating the involvement of the NMDA receptor in the antitumor effect of this compound. Due to its interesting biological profile, (S)-1 represents a lead compound to develop novel antitumor agents for breast cancer treatment.